Comparing Optimizer Strategies For Enhancing Emotion Classification In IndoBERT Models - Krisna, Julius Immanuel Theo; Luthfiarta, Ardytha; Cahya, Leno Dwi; Winarno, Sri; Nugraha, Adhitya (Universitas PGRI Semarang, 2024)
Emotions are one of the reactions of human when they receive physical or verbal action. Every human action is based on emotion. Every opinion expressed in the comments column also contains the author's emotions. This research aims to classify five emotions, Marah, Takut, Senang, Cinta, and Sedih and evaluate the performance of three commonly used optimizer, Adam, RMSProp, and Nadam. The processed data used IndoBERT model for Indonesian text classification. The research purpose to search the best optimizer for text classification. The result shows classification used Adam Optimizer 90,21%, RMSProp Optimizer 82.11, and Nadam Optimizer 88.61%. The Adam optimizer applied to the IndoBERT model yielded the best results. This shows a significant improvement from previous studies, which had emotion classification.